Description of Pαnonychus cαricαe new species on fig-trees in Greece (Acari: Tetranychidae) - Hatzinikolis Ε.Ν. (ENTOMOLOGIA HELLENICA, 1984)
The female and male of Panonychus caricae, new species, are described and illustrated. This mite was found on leaves of fig-trees in regions of Central Greece.